Reliability, Maintainability and Availability Analysis of Solar Power Plant in Pantai Baru using Voltage Measurement Data - Patricia Fitrianingtyas; Muhammad Khamim Asy’ari; Neny Elyawati (Westscience Press, 2023)
The hybrid power plant in Pantai Baru, Yogyakarta stands as a noteworthy exemplar within the realm of existing solar power installations throughout Indonesia. Analysis of reliability, maintenance, and availability is needed to minimize problems at solar power plant’s electrical energy production process, so that renewable energy security and sustainability can be maintained. This study aims to determine the reliability, maintainability, and availability of solar panels with a capacity of 48 Volts at the hybrid power plant, Pantai Baru using the control chart method, Weibull distribution. Calculation of reliability, maintainability, and availability of solar panels is carried out using solar panel output voltage measurement data collected over the last 4 years. Time to failure, TTF and time to repair, TTR were obtained from out-of-scope data on the control chart and processed using software, namely Reliasoft Weibull ++ Version 6. The simulation results and calculations show that the distribution obtained from TTF and TTR is a three-parameter Weibull distribution, with a system reliability value of 0.3, maintainability value is 1 and availability value is 0.997 in day 5th. The reliability of each solar panel unit is 0.122 or 12.2%.